UJI EFEKTIFITAS EKSTRAK ETANOL DAUN JARAK PAGAR (Jatropha curcas L) TERHADAP MORTALITAS KUTU KEPALA (Pediculus humanus capitis) - Sri Kartini; Yan Hendrika; Rena Wahyudiani (JURNAL FARMASI DAN MAKANAN, 2021)
Head lice (Pediculus humanus capitis) are small parasites that live by sucking human blood causing infections of the scalp so that they experience inflammation. Efforts to eradicate head lice are to use natural insecticides, one of the plants that have the potential to be jarak pagar leaves (Jatropha curcas L). The purpose of this study was to find out the effectiveness of ethanol extract jarak pagar leaves head lice. The method used is the laboratory experimental method by spraying ethanol extract leaves at a distance fence with concentrations of 5%, 10%, and 15% against head lice. Based on the test results, the average mortality of ethanol extract of jarak pagar leaves is at a concentration of 15% which is the most effective concentration that can kill head lice with a mortality percentage of 100%, while at concentrations of 5% and 10% with mortality percentages of 40% and 60%. The results of this study can be concluded that ethanol extract of jarak pagarleaves can be a natural insecticide against head lice. .